2017
DOI: 10.1016/j.wem.2017.03.010
|View full text |Cite|
|
Sign up to set email alerts
|

Battlefield Trauma-Induced Hypothermia: Transitioning the Preferred Method of Casualty Rewarming

Abstract: For centuries, cold and wet weather has affected military combat operations leading to tremendous loss of manpower caused by cold-weather-related injuries including trench foot, frostbite, and hypothermia. The initial battlefield management of hypothermia in military personnel had not advanced significantly following many wars and conflicts until 2006. The aim of this review is to: 1) provide an overview of trauma-induced hypothermia (TIH); 2) highlight the Department of Defense strategy for the implementation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…Steps to prevent hypothermia and the risk of hypothermia-induced coagulopathy include removing wet clothing, covering the patient to avoid additional heat loss, increasing the ambient temperature, forced air warming, warm fluid therapy, and, in extreme cases, extracorporeal re-warming devices [420422]. Recently, the use of a hypothermia prevention and management kit has been advocated [423]. This kit is a low-cost, lightweight, low-volume commercial product that sustains 10 h of continuous dry heat with an oxygen-activated, self-heating liner and provides thermal insulation due to the multi-layer composite construction of the outer shell.…”
Section: Resultsmentioning
confidence: 99%
“…Steps to prevent hypothermia and the risk of hypothermia-induced coagulopathy include removing wet clothing, covering the patient to avoid additional heat loss, increasing the ambient temperature, forced air warming, warm fluid therapy, and, in extreme cases, extracorporeal re-warming devices [420422]. Recently, the use of a hypothermia prevention and management kit has been advocated [423]. This kit is a low-cost, lightweight, low-volume commercial product that sustains 10 h of continuous dry heat with an oxygen-activated, self-heating liner and provides thermal insulation due to the multi-layer composite construction of the outer shell.…”
Section: Resultsmentioning
confidence: 99%
“…The HPMK was part of the JTS theater-wide strategy for battlefield casualties and has been used extensively in military operations to decrease mortality from trauma-induced hypothermia. 65 67 System effectiveness (net body heat gain) generally depended on the mass of the insulation enclosure. 63 The 3 commercial systems were heavy and bulky and therefore only applicable at a point of care or if they could be delivered by sled or vehicle.…”
Section: Methodsmentioning
confidence: 99%
“…The US military now mandates the use of an HPMK to prevent trauma-associated hypothermia for all litter-evacuated casualties. 5 This recommendation was based on a study using a human torso model, which found less heat loss using an HPMK when compared to other methods of heat conservation, including the Ready-Heat CHB alone and a forced air method (3M Bair Hugger, St. Paul, MN). 6 A civilian study compared a CHB with other active methods of heat conservation, such as warmed intravenous fluids, during transport of trauma patients.…”
Section: How Was This Apparently Moderately Hypothermic Patient Rewar...mentioning
confidence: 99%